The influence of different levels of physical activity and sports performance on the accuracy of dynamic lower limbs balance assessment among Chinese physical education college students - Huang, Xuejuan; Yan, Zhiyang; Ma, Yong; Liu, Hua (Frontiers in Physiology, 2023)
Improving the accuracy of dynamic balance assessment can increase the efficiency of sports injury prediction. This study aimed to investigate how physical activity and sports performance affect the dynamic balance ability of lower limbs and validate whether the lower quarter Y balance test (YBT-LQ) is a reliable predictor of sports injury risk among chinese physical education college students. Totally 169 voluntary participants completed YBT-LQ at the beginning of a semester and provided some physiological information and a injury report at the end of the semester. The correlation between YBT-LQ and selected factors was analyzed. The receiver operating characteristic(ROC) and the area under curve(AUC) of the YBT-LQ composite scores were calculated to explore an optimal cutoff value for predicting sports injury risk. The YBT-LQ composite scores exhibited strong correlations with both sports performance level and sports injury, as well as a moderate correlation with physical activity level, age (negative) and metabolic equivalent(MET). The area under the receiver operating characteristic (ROC) curves for the binary classification of composite YBT-LQ scores of the left and right legs to predict sports injury risk were 0.78 and 0.74. Stratifying the study participants according to physical activity levels and sports performance levels had an effect on the AUC values of ROC curves. The optimal cutoff scores of YBT-LQ for predicting sports injury risk were variable, with values more or less than 95%. Specifically, the cutoff scores for participants with the highest level of sports performance were notably higher, reaching up to 106.5%(left) and 107.2%(right). Physical activity and sports performance could influence human dynamic balance control. Composite scores of YBT-LQ can be used with acceptable efficiency to predict sports injury. Stratifying participants based on their levels of physical activity and sports performance leads to different optimal cutoff values of the YBT-LQ composite scores in predicting sports injury. This approach is preferable to relying solely on a uniform 95% cutoff. It is recommended to analyze individuals with higher levels of sports performance, such as elite athletes, separately from those with lower levels. This is because the former group has a higher optimal cutoff value compared to the latter.